A Low-Cost Device for Measurement of Exhaled Breath for the Detection of Obstructive Lung Disease - Adil Ahmad Shahzad; Shafaq Mushtaq; Asim Waris; Syed Omer Gilani; Maha Abdallah Alnuwaiser; Mohammed Jameel; Niaz Bahadur Khan (Biosensors, 2022)
Breath sensor technology can be used in medical diagnostics. This study aimed to build a device to measure the level of hydrogen sulfide, ammonia, acetone and alcohol in exhaled breath of patients as well as healthy individuals. The purpose was to determine the efficacy of these gases for detection of obstructive lung disease. This study was conducted on a total of 105 subjects, where 60 subjects were patients of obstructive lung disease and 45 subjects were healthy individuals. Patients were screened by means of the Pulmonary Function Test (PFT) by a pulmonologist. The gases present in the exhaled breath of all subjects were measured. The level of ammonia (32.29 ± 20.83 ppb), (68.83 ± 35.25 ppb), hydrogen sulfide (0.50 ± 0.26 ppm), (62.71 ± 22.20 ppb), and acetone (103.49 ± 35.01 ppb), (0.66 ± 0.31 ppm) in exhaled breath were significantly different (p < 0.05) between obstructive lung disease patients and healthy individuals, except alcohol, with a p-value greater than 0.05. Positive correlation was found between ammonia w.r.t Forced Expiratory Volume in 1 s (FEV1) (r = 0.74), Forced Vital Capacity (FVC) (r = 0.61) and Forced Expiratory Flow (FEF) (r = 0.63) and hydrogen sulfide w.r.t FEV1 (r = 0.54), FVC (r = 0.41) and FEF (r = 0.37). Whereas, weak correlation was found for acetone and alcohol w.r.t FEV1, FVC and PEF. Therefore, the level of ammonia and hydrogen sulfide are useful breath markers for detection of obstructive lung disease.